Fuel cell catalyst, fuel cell membrane electrode assembly, and fuel cell having the fuel cell membrane electrode assembly
By using platinum, platinum alloy or core-shell catalyst and fluorine atom modified carbon materials in fuel cell catalysts, the problem of degradation of power generation performance of fuel cells during start-up, stop or load changes is solved, and efficient power output and stable performance are achieved.
Patent Information
- Application Number
- CN201980012135.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-04-25
- Filing Date
- 2019-04-15
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2039-04-15
AI Technical Summary
The power generation performance of existing fuel cell catalysts is easily degraded when starting, stopping or load changes, and the output characteristics are insufficient, making it difficult to achieve efficient power output.
Use platinum, platinum alloy or core-shell catalyst as catalytic active substances, combine carbon materials as support, and introduce fluorine atoms into the support and catalytic active substances. By optimizing the content and distribution of fluorine atoms, the specific fluorine atom ratio can be met and the catalyst can be improved. activity and stability.
The oxygen reduction reaction efficiency is significantly improved, the output characteristics of the power are enhanced, and the power generation performance reduction caused by start-up, stop or load changes is suppressed, thereby achieving high output in the high current density area.
Smart Images

Figure CN111837272B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a catalyst for a fuel cell, a method for manufacturing the same, a membrane electrode assembly for a fuel cell, and a fuel cell having the same. More specifically, the present invention relates to a catalyst for a fuel cell that has high power output characteristics and suppresses the reduction in power generation performance caused by starting, stopping, or load changes, a method for manufacturing the same, a membrane electrode assembly for a fuel cell, and a fuel cell having the same. Background Art
[0002] Fuel cells directly convert chemical energy into electrical energy. Since they only discharge water during the conversion, they have attracted much attention as a clean power generation system. Fuel cells are classified according to the type of electrolyte and electrode used. Representative fuel cells include, for example, solid polymer type, solid oxide type, phosphoric acid type, molten carbonate type, solid electrolyte type, alkaline type, etc. Among these fuel cells, solid polymer type fuel cells have a low operating temperature (usually below 100°C) and can be miniaturized. Therefore, they are used as household cogeneration systems, power sources for electric vehicles, portable power sources, and power sources for information equipment.
[0003] Solid polymer fuel cells usually have a basic structure in which a pair of gas diffusion layers and metal diaphragms are stacked in sequence on both sides of a membrane electrode assembly (MEA: Membrane Electrode Assembly). This basic structure is called a "single cell". The membrane electrode assembly has a structure in which a solid electrolyte membrane with proton conductivity is sandwiched by a pair of electrode catalyst layers, namely, an anode side electrode catalyst layer and a cathode side electrode catalyst layer. The electrode catalyst layer is usually composed of a supported catalyst and an ionomer with proton conductivity, wherein the supported catalyst is a catalytically active substance that promotes the fuel cell reaction on a conductive carrier.
[0004] A fuel gas containing hydrogen is supplied to the anode side, and an oxidant gas containing oxygen is supplied to the cathode side. The reaction shown in the following chemical reaction formula proceeds in the three-phase interface formed on the catalytically active materials on the respective electrode catalyst layers, thereby generating electricity in the polymer electrolyte fuel cell.
[0005] [Chemical formula 1]
[0006] H2→2H + +2e - (Anode side) (1)
[0007]
[0008] As such a solid polymer fuel cell, for example, Patent Document 1 discloses a fuel cell catalyst, which includes a carbonaceous material, a cation exchange resin as a solid polymer electrolyte, and catalyst metal particles, wherein the catalyst metal particles are mainly loaded on the contact surface of the proton conduction path of the carbonaceous material and the cation exchange resin. In addition, by making the thickness (A) of the cation exchange resin and the particle size (B) of the catalyst metal particles satisfy the relationship of B≤A≤B×1.2, the utilization rate of the catalyst metal is improved, and a higher output and excellent durability are obtained. However, the output of electricity in the fuel cell catalyst disclosed in Patent Document 1 is still insufficient and needs to be further improved.
[0009] In addition, Patent Document 2 discloses a method satisfying 0.8≤(F / C) S / (F / C) W ≤1.2, (where (F / C) S is the ratio of the number of fluorine atoms on the outer surface of the fluorine-containing carbon particle to the number of carbon atoms, (F / C) W (wherein the ratio of the number of fluorine atoms in the whole fluorine-containing carbon particles to the number of carbon atoms) According to Patent Document 2, platinum is loaded on a carrier composed of fluorine-containing carbon particles, and by using the fuel cell catalyst obtained thereby, a fuel cell having high power generation performance and a power generation performance that is not easily reduced even when the fuel cell is repeatedly started and stopped is obtained. However, even in the fuel cell catalyst using the fluorine-containing carbon particles disclosed in Patent Document 2, the power generation performance is still insufficient and needs to be further improved.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2012-79489
[0013] Patent Document 2: International Publication No. WO2016 / 190248 Summary of the invention
[0014] Problems to be solved by the invention
[0015] The present invention is made in view of the above-mentioned problems, and its purpose is to provide a fuel cell catalyst having high power output characteristics and suppressing the reduction of power generation performance caused by starting, stopping or load fluctuations, a manufacturing method thereof, a fuel cell membrane electrode assembly and a fuel cell equipped with the same.
[0016] Technical solutions to solve problems
[0017] In order to solve the above-mentioned technical problems, the fuel cell catalyst in the present invention comprises at least a catalytically active substance and a carrier for loading the catalytically active substance, the catalytically active substance being at least one selected from platinum, a platinum alloy, and a core-shell catalyst in which a core of a metal different from platinum is coated with a shell containing platinum, the carrier being a carbon material, and at least any one of the catalytically active substance and the carrier containing fluorine atoms.
[0018] In the above configuration, preferably, the ratio of the number of fluorine atoms contained in at least one of the catalytically active material and the carrier to the number of carbon atoms contained in the carrier satisfies the relationship represented by the following formula (1).
[0019] (F / C) S / (F / C) W <0.8···(1)
[0020] Among them, (F / C) S The ratio of the number of fluorine atoms on the surface of the fuel cell catalyst to the number of carbon atoms (F / C) W It indicates the ratio of the number of fluorine atoms to the number of carbon atoms in the entire fuel cell catalyst.
[0021] In the above configuration, preferably, the (F / C) S Less than 0.4.
[0022] In the above-mentioned constitution, preferably, the carbon material is at least one selected from graphite, graphite oxide, carbon black, graphitized carbon black, diamond-like carbon, fullerene, single-walled carbon nanotube, multi-walled carbon nanotube, carbon nanohorn, carbon nanowall, carbon nanofiber, carbon nanobrush, single-layer graphene, multi-layer graphene, and graphene oxide.
[0023] In order to solve the above-mentioned technical problems, the membrane electrode assembly for fuel cells in the present invention comprises at least a solid polymer electrolyte membrane and an electrode catalyst layer arranged on the two surfaces of the solid polymer electrolyte membrane, wherein the electrode catalyst layer comprises at least the fuel cell catalyst as described above and an ionomer covering the fuel cell catalyst.
[0024] In the above configuration, the ionomer may be a fluorine-based resin.
[0025] In the above configuration, the ionomer may be an aromatic hydrocarbon resin.
[0026] In the above configuration, the ionomer may be an ionic liquid.
[0027] In order to solve the above-mentioned problems, a fuel cell according to the present invention includes the above-mentioned fuel cell membrane electrode assembly.
[0028] Effects of the Invention
[0029] According to the present invention, there can be provided a fuel cell catalyst having high catalytic activity, which can improve the output characteristics of electricity by enhancing the oxygen reduction reaction, and can also suppress the degradation of power generation performance caused by the response to start-up, stop and load (variation), a method for manufacturing the catalyst, a membrane electrode assembly for fuel cell and a fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] FIG. 1 is a schematic cross-sectional view showing a fuel cell having a single cell structure in an embodiment of the present invention. DETAILED DESCRIPTION
[0031] (Catalysts for fuel cells)
[0032] The fuel cell catalyst in this embodiment has a structure of a support body, and the support body at least has a catalytically active substance and a support that supports the catalytically active substance. In addition, at least one of the catalytically active substance and the support contains fluorine atoms. The fuel cell catalyst in this embodiment can be appropriately used in solid polymer fuel cells, etc.
[0033] <Carrier>
[0034] First, the support constituting the fuel cell catalyst will be described.
[0035] In this specification, “support” refers to an electronically conductive substance used to suppress excessive aggregation of catalytically active materials in an anode electrode catalyst layer and / or a cathode electrode catalyst layer (hereinafter, sometimes simply referred to as “electrode catalyst layer”).
[0036] The carrier of the present embodiment is composed of a carbon material. As a carbon material, there is no particular limitation, for example, activated carbon, carbon black, graphitized carbon black, hard carbon, soft carbon, mesoporous carbon, natural graphite, artificial graphite, diamond-like carbon, fullerene, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanohorns, carbon nanowalls, carbon nanofibers, carbon nanobrush, monolayer graphene, multilayer graphene, graphene oxide, etc. They can be used alone or in combination of two or more. From the viewpoint of electrical conductivity, chemical stability, and easy availability, preferably carbon black, graphitized carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, monolayer graphene, and multilayer graphene.
[0037] The specific surface area of the carbon material may be sufficient to support the catalytically active material in a highly dispersed manner, and specifically, it is preferably 10 to 1500 m 2 / g, more preferably 30 to 1200 m 2 / g, particularly preferably 50 to 1000 m 2 / g. By making the specific surface area 10m 2 / g or more, the catalytically active material is loaded on the carrier in large quantities, and the performance of the fuel cell is improved. On the other hand, by making the specific surface area 1500m 2 / g or less, the utilization rate of the supported catalytically active material can be suppressed from decreasing. It should be noted that the specific surface area of the carbon material can be measured, for example, by the BET method in accordance with Japanese Industrial Standard JIS Z8830:2013.
[0038] In the case where the carrier contains fluorine atoms, for example, when the ionomer (described in detail later) contains fluorine atoms, the affinity of the carrier to the ionomer can be improved. Improving the affinity with the ionomer means, for example, promoting the state of oxygen diffusion and proton diffusion cited as rate-limiting factors at the three-phase interface in the electrode catalyst layer (the interface where the three phases of reaction gas composed of fuel cell catalyst, solid polymer electrolyte, and oxygen (oxidant) or hydrogen (reducing agent) are in contact). In existing fuel cells, oxygen and protons in the mass transfer process in the high current density region produce a movement limit, thereby resulting in reduced battery performance. However, by promoting the diffusion of oxygen and protons, their movement limit can be reduced, and as a result, the oxygen reduction reaction can be improved to achieve high output in the high current density region.
[0039] In addition, the presence of fluorine atoms on the outer surface of the carbon material and / or the inner surface of the pores can reduce or inhibit the corrosion of the carbon material. As a result, when starting and stopping the fuel cell, the catalytic active material can be reduced from being separated due to the corrosion of the carbon material, and the reduction in power generation performance due to repeated starting and stopping of the fuel cell can be inhibited.
[0040] As the content of the fluorine atoms, relative to the total mass of the fuel cell catalyst, it is preferably 0.1 to 30 mass%, more preferably 0.25 to 20 mass%, and particularly preferably 0.5 to 15 mass%. By making the content of fluorine atoms 0.1 mass% or more, as described above, it is possible to suppress the reduction in power generation performance caused by repeated start-up and shutdown of the fuel cell. In addition, a fuel cell that achieves high output of electricity in a high current density region can be obtained. On the other hand, by making the content of fluorine atoms 30 mass% or less, it is possible to suppress the reduction in conductivity.
[0041] The fluorine atoms exist in a state of being adsorbed on the outer surface of the carbon material or the inner surface of the pores by, for example, chemical adsorption and / or physical adsorption.
[0042] In addition, the fluorine atoms are preferably uniformly present on the outer surface of the carbon material. Further, the fluorine atoms are preferably also uniformly present inside the pores of the carbon material. Thus, on the outer surface of the carbon material and the inner surface of the pores, it is possible to suppress the corrosion of the carbon material in the region where the fluorine atoms are not present.
[0043] <Catalytically active substances>
[0044] Next, the catalytically active material in this embodiment will be described below.
[0045] In this specification, "catalytically active material" refers to a material that can function as a catalyst in an electrochemical reaction in a fuel cell. Specifically, the catalytically active material of this embodiment is composed of at least one active species selected from platinum, platinum alloys, and core-shell catalysts.
[0046] In the platinum alloy, the metal alloyed with platinum is not particularly limited, and for example, boron, magnesium, aluminum, silicon, calcium, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, strontium, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, indium, tin, antimony, barium, hafnium, tantalum, tungsten, rhenium, osmium, iridium, gold, lead, bismuth, lanthanum, cerium, etc. These metals can be used alone or in combination of two or more to form a platinum alloy. It should be noted that, as the metal alloyed with platinum, from the viewpoint of catalyst performance, preferably ruthenium, molybdenum, osmium, cobalt, rhodium, iridium, iron, nickel, titanium, tungsten, palladium, rhenium, chromium, manganese, tantalum and gold.
[0047] The content of platinum in the platinum alloy is preferably in the range of 1 to 99 mass %, more preferably in the range of 3 to 75 mass %, and particularly preferably in the range of 5 to 50 mass %, relative to the total mass of the platinum alloy. If the content of platinum is 1 mass % or more, the catalyst function in the fuel cell reaction can be improved. On the other hand, if the content of platinum is 99 mass % or less, it can form an alloy with metals other than platinum.
[0048] The core-shell catalyst is a catalyst formed by coating a core composed of a metal other than platinum with a shell containing platinum. As the metal constituting the core, as long as it is not platinum, it is not particularly limited, for example, it can be enumerated: nickel, copper, palladium, silver, gold, iridium, titanium, iron, cobalt, ruthenium, osmium, chromium, molybdenum, tungsten. Among these metals, nickel, copper, palladium, silver, gold, iridium, titanium, iron, cobalt, ruthenium are preferred from the viewpoint of catalyst performance. In addition, these metals can be used only one, or two or more can be used in combination.
[0049] The shell is not particularly limited as long as it contains at least platinum. For example, in addition to being composed of platinum alone, the shell may contain platinum and at least one of nickel, copper, palladium, silver, or gold.
[0050] When the catalytically active substance contains other fluorine atoms, the other fluorine atoms are present in a state of being adsorbed on the surface of the catalytically active substance by chemical adsorption and / or physical adsorption.
[0051] By making the catalytically active material contain other fluorine atoms, for example, when using a carbon material and / or ionomer containing fluorine atoms, the affinity with the carbon material etc. can be improved. Thus, for example, at the three-phase interface in the electrode catalyst layer, a state is formed that promotes oxygen diffusion and proton diffusion cited as the rate-limiting factor. As a result, similarly to the above-mentioned situation, the movement rate limit of oxygen and protons can be further reduced, the oxygen reduction reaction can be improved, and high output in the high current density region can be achieved.
[0052] When the catalytically active material contains other fluorine atoms, the content of the other fluorine atoms is preferably 0.1 to 30% by mass, more preferably 0.25 to 20% by mass, and particularly preferably 0.5 to 10% by mass, relative to the total mass of the fuel cell catalyst, based on the total amount of the fluorine atoms contained in the carbon material as a carrier. By making the total content of the other fluorine atoms and fluorine atoms 0.1% by mass or more, as described above, it is possible to suppress the reduction in power generation performance caused by repeated start-up and shutdown of the fuel cell. In addition, a fuel cell capable of achieving high output in a high current density region can be obtained. On the other hand, by making the total content of the other fluorine atoms and fluorine atoms 30% by mass or less, it is possible to suppress the reduction in conductivity.
[0053] The average particle size of the catalytically active substance supported on the carbon material is not particularly limited, and is generally 0.1 to 50 nm, preferably 0.5 to 30 nm, and more preferably 1 to 20 nm. By making the average particle size of the catalytically active substance greater than 0.1 nm, the catalyst activity can be improved. On the other hand, by making the average particle size of the catalytically active substance less than 50 nm, the active sites can be suppressed from decreasing as the specific surface area of the catalytically active substance decreases. It should be noted that the average particle size of the catalytically active substance represents the value obtained by measuring the diameter of the circumscribed circle of the catalytically active substance and averaging it. Specifically, the average particle size is a value calculated from the average value of the particle sizes of at least 500 catalytically active substances dispersed in a field of view of 500 nm × 500 nm in an observation image obtained by a transmission electron microscope or a scanning electron microscope.
[0054] In addition, the maximum particle size of the catalytically active substance supported on the carbon material is not particularly limited, and is generally 0.1 to 60 nm, preferably 0.5 to 30 nm, and more preferably 1 to 20 nm. By making the maximum particle size of the catalytically active substance greater than 0.1 nm, the catalytic activity per unit catalyst mass can be increased by increasing the reaction surface area. On the other hand, by making the maximum particle size of the catalytically active substance less than 60 nm, the active sites can be suppressed from decreasing as the specific surface area of the catalytically active substance decreases. More specifically, the maximum particle size represents the particle size of particles with the maximum particle size that can be seen in a field of view of 500 nm × 500 nm.
[0055] It should be noted that the average particle size and maximum particle size of the catalytically active material refer to the values obtained by measuring the particle size using the value of the major axis when the shape is other than spherical, such as elliptical, and using the equivalent circle diameter as the particle size when the shape is other than spherical.
[0056] In addition, the content of the catalytically active substance is not particularly limited, and is generally 5 to 80% by mass, preferably 10 to 75% by mass, and more preferably 15 to 70% by mass, relative to the total mass of the fuel cell catalyst. By making the content of the catalytically active substance 5% or more by mass, it is possible to maintain high catalyst activity. On the other hand, by making the content of the catalytically active substance 80% or less by mass, it is possible to suppress the reduction in the proportion of the catalytically active substance that is effectively utilized. In addition, it is also possible to suppress the aggregation of the catalytically active substance supported on the carrier, and the resulting reduction in catalyst activity.
[0057] <Ratio of the number of fluorine atoms to the number of carbon atoms in the fuel cell catalyst>
[0058] In the present embodiment, preferably, the ratio of the number of fluorine atoms contained in at least one of the catalytically active material and the carrier to the number of carbon atoms as the carrier satisfies the relationship of the following formula (1).
[0059] (F / C) S / (F / C) W <0.8···(1)
[0060] (Among them, (F / C) S The ratio of the number of fluorine atoms on the surface of the fuel cell catalyst to the number of carbon atoms (F / C) W It represents the ratio of the number of fluorine atoms to the number of carbon atoms in the entire fuel cell catalyst.
[0061] By making the ratio of the number of carbon atoms to the number of fluorine atoms satisfy the relationship shown in formula (1), it is possible to suppress the decrease in the conductivity of the fuel cell catalyst and achieve excellent catalyst activity.S / (F / C) W The value of is preferably 0.1 or more and less than 0.8, and more preferably 0.3 or more and less than 0.8.
[0062] It should be noted that (F / C) S The value of can be calculated using X-ray photoelectron spectroscopy (XPS). W It can be calculated by the combustion flask method. That is, the fuel cell catalyst is burned in a flask filled with oxygen, and the generated gas is absorbed into the sample liquid in the flask. The fluorine ions dissolved in the sample liquid by absorbing the gas are measured by ion chromatography. In this way, the (F / C) can be calculated. W The value of .
[0063] As described (F / C) S The upper limit of (F / C) is preferably less than 0.4, more preferably less than 0.3, further preferably less than 0.2, and particularly preferably less than 0.1. S The upper limit of (F / C) is less than 0.3, which can suppress the decrease in conductivity and form a surface with oxidation resistance. S The lower limit of is preferably 0.001 or more.
[0064] <Work Function of Fuel Cell Catalyst>
[0065] The work function of the fuel cell catalyst in this embodiment is preferably 4 to 7.5 eV, more preferably 4 to 7 eV, and particularly preferably 5 to 6.5 eV. If the work function of the fuel cell catalyst is 4 eV or more, the electronic conductivity can be well maintained. On the other hand, if the work function of the fuel cell catalyst is 7.5 eV or less, the oxidation resistance can be improved without impairing the electronic conductivity. It should be noted that the work function of the fuel cell catalyst can be measured by ultraviolet photoelectron spectroscopy, etc.
[0066] (Method for producing fuel cell catalyst)
[0067] Next, a method for producing the fuel cell catalyst in this embodiment will be described below.
[0068] As the method for producing the fuel cell catalyst in this embodiment, there are: method A in which a catalytically active substance is loaded on a carrier after fluorination treatment, method B in which a catalytically active substance is loaded on a carrier and then fluorinated, and method C in which the catalytically active substance after fluorination treatment is loaded on a carrier. In this embodiment, the method A and the method B may be re-fluorinated.
[0069] <Support of Catalytically Active Substance>
[0070] There is no particular limitation on the method of loading the catalytically active substance on the carrier, and a known method can be used. For example, a carbon material as a carrier is dispersed in a reaction solution in which a precursor of the catalytically active substance is dissolved. There is no particular limitation on the dispersion method, and a known method can be used. Next, a suitable reducing agent is added to the reaction solution to reduce the metal ion species of the dissolved precursor, thereby loading the catalytically active substance on the surface of the carrier. Next, after the reaction solution is subjected to solid-liquid separation, the solid component is dried. Thus, a support of the catalytically active substance is obtained. It should be noted that, regardless of whether fluorine atoms are introduced into the catalytically active substance and the carbon material, the catalytically active substance can be loaded on the carbon material.
[0071] For example, when the catalytically active substance is a single metal platinum and the carbon material is carbon black, chloroplatinic acid and its salts are dissolved in water as a precursor of platinum to prepare a reaction solution. Next, the carbon black is added to the reaction solution and dispersed, and then a reducing agent is added. The reducing agent is not particularly limited, and for example, sodium borohydride, hydrazine, formaldehyde, alcohol, etc. can be cited. By adding a reducing agent, microparticles of platinum are reduced and precipitated on the surface of the carbon black. Next, the reaction solution is subjected to solid-liquid separation, and the solid component is dried, thereby making it possible to prepare a support of the catalytically active substance in which microparticles of platinum are supported on the surface of the carbon black and inside the pores.
[0072] <Introduction of fluorine atoms>
[0073] Fluorine atoms can be introduced into a catalytically active substance, a carbon material, or a carbon material loaded with a catalytically active substance by fluorination. By fluorination, a fluorine group based on a carbon-fluorine bond is introduced into the surface of the carbon material or the inside of the pores. Therefore, for example, unlike an oxidation treatment that imparts oxygen-containing functional groups such as hydroxyl, carbonyl or carboxyl to the edge of the carbon hexagonal mesh, the surface can be fluorinated without causing structural defects such as damage to the carbon material or decomposition thereof.
[0074] The method of fluorination treatment is not particularly limited, and examples thereof include: a method of bringing a treatment gas containing fluorine atom-containing gas into contact with a treatment object such as a catalytically active substance, a method of bringing a treatment liquid obtained by dissolving fluorine atom-containing gas in a solvent into contact with a treatment object, a method of bringing a treatment liquid obtained by dissolving a fluorinating agent in a solvent into contact with a treatment object, etc.
[0075] As the processing gas, a processing gas containing 0.1 to 100 vol%, preferably 0.2 to 80 vol%, and more preferably 0.3 to 50 vol% of fluorine atom-containing gas relative to the total volume is used. By making the concentration of the fluorine atom-containing gas 0.1 vol% or more, insufficient fluorine atoms introduced into the processing object such as the catalytically active material can be prevented.
[0076] Fluorine-containing atom gas refers to a gas containing fluorine atoms. In the present embodiment, as long as it is a gas containing fluorine atoms, it is not particularly limited. As fluorine-containing atom gas, for example, fluorine (F2), hydrogen fluoride (HF), chlorine trifluoride (ClF3), bromine trifluoride (BrF3), bromine pentafluoride (BrF5), iodine pentafluoride (IF5), phosphorus pentafluoride (PF5), sulfur tetrafluoride (SF4), boron trifluoride (BF3), nitrogen trifluoride (NF3), carbonyl fluoride (COF2), etc. They can be used alone or in combination of two or more.
[0077] The processing gas may also contain an inert gas. There is no particular limitation on the inert gas, but it is not preferred to use a gas that reacts with a fluorine atom-containing gas to adversely affect the fluorination treatment of the carbon material, a gas that reacts with the carbon material to adversely affect, and a gas containing impurities that produce the adverse effect. Specifically, for example, nitrogen, argon, helium, neon, krypton, xenon, etc. can be mentioned. They can be used alone or in combination of two or more. In addition, the purity of the inert gas is not particularly limited, but for impurities that produce the adverse effect, it is preferably less than 100 ppm, more preferably less than 10 ppm, and particularly preferably less than 1 ppm.
[0078] In addition, the processing gas may also include a halogen atom-containing gas (but excluding a fluorine atom-containing gas). Examples of the halogen atom-containing gas include chlorine gas and bromine gas. These gases may be used alone or in combination of two or more.
[0079] The method of bringing the processing gas into contact with the processing target such as the catalytically active material is not particularly limited, and the processing gas may be brought into contact with the processing target while the processing gas is flowing or in a sealed state.
[0080] In the method of bringing the treatment liquid prepared by dissolving the fluorine atom-containing gas in the solvent into contact with the carbon material, the solvent is not particularly limited, and an aprotic polar solvent or a protic polar solvent can be used.
[0081] The aprotic polar solvent is not particularly limited, and examples thereof include hexane, benzene, toluene, chloroform, dichloromethane, acetone, methyl ethyl ketone, methyl acetone, methyl isobutyl ketone, diisobutyl ketone, cyclohexanone, tetrahydrofuran, diisopropyl ether, dibutyl ether, 1,4-dioxane, 1,3-dioxolane, dimethoxyethane, ethylene glycol dimethyl ether, γ-butyrolactone, γ-valerolactone, acetonitrile, propionitrile, dimethyl sulfoxide, dimethyl sulfone, cyclopentane, 1,3-propane sultone, dimethyl sulfate, trimethyl phosphate, triethyl phosphate, N,N-dimethylformamide, N-methyl-2-pyrrolidone, methyl acetate, ethyl acetate, butyl acetate, propylene carbonate, ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, etc. These solvents can be used alone or in combination of two or more.
[0082] The protic polar solvent is not particularly limited, and examples thereof include water, acetic acid, formic acid, methanol, ethanol, isopropanol, butanol, nitromethane, nitroethane, etc. These can be used alone or in combination of two or more.
[0083] The concentration of the fluorine atom-containing gas in the treatment liquid is not particularly limited, but is generally 0.1 to 100 mass %, preferably 0.2 to 80 mass %, and more preferably 0.3 to 50 mass %, relative to the total mass of the treatment liquid. By making the concentration of the fluorine atom-containing gas 0.1 wt % or more, insufficient fluorine atoms introduced into the treatment object such as the catalytically active material can be suppressed.
[0084] In the method of contacting a treatment liquid prepared by dissolving a fluorinating agent in a solvent with a treatment object such as a catalytically active substance, the fluorinating agent is not particularly limited, and examples thereof include potassium fluoride, acidic potassium fluoride, tetrabutylammonium fluoride hydrate, tetrabutylammonium difluoride, tetrabutyldihydrogentrifluoroammonium, tetramethylammonium fluoride tetrahydrate, 1-fluoropyridine tetrafluoroborate, 1-fluoropyridine trifluoromethanesulfonate, 1-fluoro-2,4,6-trimethylpyridine trifluoromethanesulfonate, fluorinating agent F-51, etc. These can be used alone or in combination of two or more.
[0085] The solvent for dissolving the fluorinating agent is not particularly limited, and the above-mentioned aprotic polar solvents and protic polar solvents can be used. Therefore, detailed description thereof is omitted.
[0086] The concentration of the fluorinating agent in the treatment liquid is not particularly limited, but is generally 0.1 to 100 mass %, preferably 0.2 to 80 mass %, and more preferably 0.3 to 50 mass % relative to the total mass of the treatment liquid. By making the concentration of the fluorinating agent 0.1 mass % or more, insufficient fluorine atoms introduced into the treatment object such as the catalytically active material can be prevented.
[0087] The treatment temperature during the fluorination treatment is preferably -50°C to 600°C, more preferably -20°C to 350°C, further preferably -10°C to 250°C, and particularly preferably -10°C to 100°C. By making the treatment temperature above -50°C, fluorine atoms can be introduced into the treatment object such as the catalytically active material. On the other hand, by making the treatment temperature below 600°C, it is possible to prevent the formation of CF4 due to the fluorination of the carbon material and the consumption of carbon. In addition, it is possible to prevent the conductivity of the fuel cell catalyst from being reduced and the volume from being increased due to the sintering of the catalytically active material.
[0088] The treatment time (reaction time) of the fluorination treatment is not particularly limited, as long as fluorine atoms can be uniformly introduced into the treatment object such as the catalytically active material. The treatment time is usually preferably 0.5 minutes to 12 hours. By making the treatment time more than 0.5 minutes, the surface and pores of the carbon material can be fully fluorinated. On the other hand, by making the treatment time less than 12 hours, the manufacturing efficiency can be prevented from being reduced due to the long-term manufacturing time.
[0089] The pressure conditions for the fluorination treatment are not particularly limited, and the treatment can be carried out under normal pressure, under pressure or under reduced pressure. From the viewpoint of economy and safety, the treatment is preferably carried out under normal pressure. The reaction vessel for the fluorination treatment is not particularly limited, and a conventionally known vessel such as a fixed bed or a fluidized bed can be used.
[0090] In addition, it is preferred that the catalytically active material or other treatment object is subjected to a decompression treatment immediately before and / or immediately after the fluorination treatment. As a method for decompression treatment, for example, a method of evacuating the treatment object in a reaction vessel can be cited. Thus, it is possible to remove moisture attached to the surface of the carbon material as a carrier, unreacted treatment gas (including unreacted fluorine atom-containing gas, etc.), and reaction byproducts produced as byproducts by the fluorination treatment.
[0091] The pressure condition for the reduced pressure treatment is preferably in the range of 0 Pa to 100 Pa, more preferably in the range of 0 Pa to 50 Pa, and particularly preferably in the range of 0 Pa to 10 Pa. By setting the pressure to 100 Pa or less, as described above, moisture adhering to the surface of the carrier, unreacted treatment gas, and reaction byproducts produced as by-products by the fluorination treatment can be removed.
[0092] The treatment time of the reduced pressure treatment is not particularly limited, but is usually in the range of 10 minutes to 2 hours, preferably 10 minutes to 1.5 hours, and more preferably 10 minutes to 1 hour.
[0093] <Re-fluorination>
[0094] The refluorination treatment is a step for introducing fluorine atoms into a material in which a fluorinated catalytically active substance is supported on an unfluorinated carbon material or a material in which an unfluorinated catalytically active substance is supported on a fluorinated carbon material.
[0095] In the refluorination treatment, the same method as the above-mentioned fluorination treatment can be used. In addition, the treatment conditions in the refluorination treatment, specifically, the type of treatment gas or treatment liquid, the concentration of fluorine atoms in the treatment gas and treatment liquid, the treatment temperature, the treatment time and the treatment pressure, can also be appropriately changed as needed within the range of the treatment conditions described in the above-mentioned fluorination treatment.
[0096] Furthermore, in the case of refluorination, it is also preferred to decompress the object before and / or immediately after the treatment. The method of decompression treatment is the same as in the above case. Thus, it is possible to remove moisture attached to the surface of the carbon material, unreacted treatment gas (including unreacted fluorine atom-containing gas, etc.), and reaction byproducts produced by the fluorination treatment.
[0097] (Fuel Cell)
[0098] Next, a fuel cell using the fuel cell catalyst of the present embodiment will be described below based on Fig. 1. Fig. 1 is a schematic cross-sectional view showing a fuel cell having a single cell structure in the present embodiment.
[0099] As shown in FIG. 1 , the fuel cell unit cell 1 of the present embodiment includes at least a membrane electrode assembly (MEA: Membrane Electrode Assembly) 10, a pair of gas diffusion layers 13, a pair of diaphragms 14, and a gasket 15. The pair of gas diffusion layers 13 are respectively composed of an anode-side gas diffusion layer 13a and a cathode-side gas diffusion layer 13b, which are stacked on both surfaces of the membrane electrode assembly 10 in a manner of sandwiching the membrane electrode assembly 10. In addition, a pair of diaphragms 14 are stacked in a manner of sandwiching the anode-side gas diffusion layer 13a and the cathode-side gas diffusion layer 13b. The gasket 15 is arranged in a manner of covering a polymer electrolyte membrane (described in detail later) located at the periphery of the membrane electrode assembly 10.
[0100] It should be noted that the fuel cell 1 can be used, for example, in a single cell stack structure in which a plurality of fuel cell 1 are stacked in series via a connecting member. This can achieve a high-output fuel cell.
[0101] <Membrane Electrode Assembly for Fuel Cell>
[0102] The membrane electrode assembly 10 of this embodiment comprises at least a solid polymer electrolyte membrane 11 and a pair of electrode catalyst layers 12 provided on both surfaces of the solid polymer electrolyte membrane 11, more specifically, an anode side electrode catalyst layer (fuel electrode) 12a and a cathode side electrode catalyst layer (air electrode) 12b.
[0103] The solid polymer electrolyte membrane 11 preferably has proton conductivity and electronic insulation. As the solid polymer electrolyte membrane 11, a membrane composed of a known material such as a polymer or copolymer having high proton conductivity and ion exchange groups can be used. Specifically, for example, a fluorine-based resin in which a part or all of the polymer skeleton is fluorinated or an aromatic hydrocarbon resin containing no fluorine atoms in the polymer skeleton can be cited.
[0104] The fluorine-based resin is not particularly limited, and examples thereof include perfluorocarbon sulfonic acid polymers such as Nafion (registered trademark, DuPont Co., Ltd.), Aciplex (registered trademark, Asahi Kasei Corporation), Flemion (registered trademark, Asahi Glass Co., Ltd.), and GORE-SELECT (registered trademark, GORE Co., Ltd.), polytrifluorostyrene sulfonic acid polymers, perfluorocarbon phosphonic acid polymers, trifluorostyrene sulfonic acid polymers, ethylene tetrafluoroethylene-g-styrene sulfonic acid polymers, ethylene-tetrafluoroethylene copolymers, polytetrafluoroethylene-g-polystyrene sulfonic acid polymers, and polyvinylidene fluoride-g-polystyrene sulfonic acid polymers.
[0105] The aromatic hydrocarbon resin is not particularly limited, and examples thereof include polysulfone sulfonic acid polymers, polyetheretherketone sulfonic acid polymers, polybenzimidazolyl sulfonic acid polymers, polybenzimidazolyl phosphonic acid polymers, crosslinked polystyrene sulfonic acid polymers, and polyethersulfone sulfonic acid polymers.
[0106] The thickness of the solid polymer electrolyte membrane 11 is not particularly limited, and is generally 5 to 300 μm, preferably 10 to 200 μm. If the thickness of the solid polymer electrolyte membrane 11 is 5 μm or more, sufficient mechanical strength can be ensured when the membrane electrode assembly 10 is formed. On the other hand, if the thickness of the solid polymer electrolyte membrane 11 is 300 μm or less, the membrane resistance of the solid polymer electrolyte membrane 11 can be reduced, thereby improving the power generation performance.
[0107] The anode side electrode catalyst layer 12a and the cathode side electrode catalyst layer 12b as the electrode catalyst layer 12 each include at least the fuel cell catalyst of the present embodiment and an ionomer (electrolyte layer) covering the fuel cell catalyst and having proton conductivity. The anode side electrode catalyst layer 12a and the cathode side electrode catalyst layer 12b each have pores, so that, for example, hydrogen can be diffused inside the anode side electrode catalyst layer 12a. In addition, in the cathode side electrode catalyst layer 12b, oxygen can be diffused inside, or water generated by the reduction reaction of oxygen molecules can be passed through.
[0108] In the anode-side electrode catalyst layer 12a, the ionomer functions as a path (channel) for protons generated by the oxidation reaction of hydrogen molecules to move to the solid polymer electrolyte membrane 11. On the other hand, in the cathode-side electrode catalyst layer 12b, the ionomer functions as a path for the protons that have passed through the solid polymer electrolyte membrane 11 to move to the vicinity of the supported catalytically active material.
[0109] As ionomers, for example, fluorine resins, aromatic hydrocarbon resins, ionic liquids, etc. can be cited. As fluorine resins and aromatic hydrocarbon resins, the same substances as those used in the above-mentioned solid polymer electrolyte 11 can be used. In the case of using a substance composed of a fluorine resin as an ionomer, when the carrier (carbon material) in the fuel cell catalyst of the present embodiment contains fluorine atoms, the affinity of the ionomer and the fuel cell catalyst can be improved. Thus, for example, a state of promoting oxygen diffusion and proton diffusion cited as rate-limiting factors is formed in the three-phase interface on the electrode catalyst layer. As a result, the oxygen reduction reaction can be improved to achieve high output in the high current density region.
[0110] The ionic liquid is not particularly limited, but preferably has high proton conductivity, maintains a liquid state in a temperature range of -30°C to 200°C, has little change in physical properties even at high temperatures of 400°C or higher, has high heat resistance, and has low vapor pressure. Specifically, the ionic liquid is composed of a cationic component and an anionic component.
[0111] Examples of the cationic component include quaternary ammonium cations, tertiary ammonium cations, secondary ammonium cations, imidazolium cations, pyrazolium cations, pyridinium cations, phosphonium cations, and sulfonium cations.
[0112] Examples of the quaternary ammonium cation include tetraethylammonium, tetrapropylammonium, tetraisopropylammonium, trimethylethylammonium, diethyldimethylammonium, methyltriethylammonium, trimethylpropylammonium, trimethylisopropylammonium, tetrabutylammonium, trimethylbutylammonium, trimethylpentylammonium, trimethylhexylammonium, butyltriethylammonium, triethylpentylammonium, tetrabutylammonium, tributylmethylammonium, ethyldimethylpropylammonium, methyltrioctylammonium, diethyl-2-methoxyethylmethylammonium, ethyl-2-methoxyethyldimethylammonium, Methylammonium, ethyl-3-methoxypropyldimethylammonium, benzylethyldimethylammonium, ethyldimethyl-2-phenylethylammonium, 1-methyl-1-propylpyrrolidinium, 1-butyl-1-methylpyrrolidinium, 1-methoxymethyl-1-methylpyrrolidinium, 1-(2-methoxyethyl)-1-methylpyrrolidinium, 1-allyl-1-methylpyrrolidinium, 1-methyl-1-propylpiperidinium, 1-butyl-1-methylpiperidinium and the like.
[0113] Examples of the tertiary ammonium cation include trimethylammonium, triethylammonium, tripropylammonium, tributylammonium, dimethylethylammonium, methyldiethylammonium, triisopropylammonium, dimethylisopropylammonium, diethylisopropylammonium, dimethylpropylammonium, dimethylbutylammonium, 1-methylpyrrolidinium, 1-ethylpyrrolidinium, 1-propylpyrrolidinium, 1-butylpyrrolidinium, 1-methylpiperidinium, 1-ethylpiperidinium, 1-propylpiperidinium, and 1-butylpiperidinium.
[0114] Examples of the secondary ammonium cation include dimethylammonium, diethylammonium, dipropylammonium, diisopropylammonium, dibutylammonium, ethylmethylammonium, methylisopropylammonium, ethylisopropylammonium, butylmethylammonium, pyrrolidinium, and piperidinium.
[0115] Examples of the imidazolium cation include 1,3-dimethylimidazolium, 1-ethyl-3-methylimidazolium, 1-methyl-3-octylimidazolium, 1-methyl-3-propylimidazolium, 1-butyl-3-methylimidazolium, 1-hexyl-3-methylimidazolium, 1-ethyl-2,3-dimethylimidazolium, 1-butyl-2,3-dimethylimidazolium, 1-allyl-3-methylimidazolium, 1-methylimidazolium, 1-ethylimidazolium, 1-vinylimidazolium, 1-allylimidazole, 2-methylimidazolium, and imidazolium.
[0116] Examples of the pyrazolium cation include 1,2-dimethylpyrazolium, 1-methyl-2-ethylpyrazolium, 1-propyl-2-methylpyrazolium, 1-methyl-2-butylpyrazolium, 1,3-dimethylpyrazolium, 1,5-dimethylpyrazolium, 1-methylpyrazolium, 1-ethylpyrazolium, 3-methylpyrazolium, 4-methylpyrazolium, pyrazolium, 3,5-dimethylpyrazolium, pyrazolium, 4-iodopyrazolium, 4-bromopyrazolium, 4-iodo-1-methylpyrazolium, 4-bromo-1-methylpyrazolium, 5-iodo-1-methylpyrazolium, 5-bromo-1-methylpyrazolium, 3-iodopyrazolium, 3-bromopyrazolium, 3-trifluoromethylpyrazolium, 3-methyl-5-trifluoromethylpyrazolium and the like.
[0117] Examples of the pyridinium cation include 1-methylpyridinium, 1-ethylpyridinium, 1-propylpyridinium, 1-butylpyridinium, 1-ethyl-3-methylpyridinium, and pyridinium.
[0118] Examples of the phosphonium cation include butyltriethylphosphonium, triethylpentylphosphonium, triethyloctylphosphonium, triethylmethoxymethylphosphonium, triethyl(2-methoxyethyl)phosphonium, tributylmethylphosphonium, tributylethylphosphonium, tributyloctylphosphonium, tributylmethoxymethylphosphonium, and tributyl(2-methoxyethyl)phosphonium.
[0119] Examples of the sulfonium cation include trimethylsulfonium, triphenylsulfonium, and triethylsulfonium.
[0120] The cationic components exemplified above can be used alone or in combination of two or more.
[0121] Examples of the anion component include halogen anions, fluorine-containing anions, cyanide-containing anions, fluorine-free phosphoric acid derivative anions, fluorine-free sulfuric acid derivative anions, and the like.
[0122] Examples of the halogen anion include: Cl - Br - ,I - wait.
[0123] As the fluorine-containing anion, for example, BF4 - 、BF3CF3 - 、BF3C2F5 - PF6 - PO2F2 - PO2(CF3CH2O)2 - CF3SO3 - 、C2F5SO3 - 、C3F7SO3 - 、C4F9SO3 - 、N(SO2F)2 - 、N(CF3SO2)2 - 、N(C2F5SO2)2 - 、N(CF3SO2)(CF3CO) - 、N(CF3SO2)(C2F5SO2) - 、C(CF3SO2)3 - , (HF) x F - (X is 1.0 to 2.3), SbF6 - 、AsF6 - CF3COO - wait.
[0124] Examples of the cyanide-containing anion include: SCN - 、B(CN)4 - 、N(CN)2 - 、C(CN)3 - wait.
[0125] As the fluorine-free phosphoric acid derivative anion, for example, PO2(OCH3)2 - PO2(OC2H5)2 - PO2[OCH(CH3)2]2 - PO2(OC4H9)2 - 、HPO2(OCH3) - 、HPO2(OC2H5) - 、HPO2[OCH(CH3)2] - 、HPO2(OC4H9) - .
[0126] As the sulfuric acid derivative anion not containing fluorine, for example, there can be mentioned: CH3SO3 - 、C2H5SO3 - 、SO3(OCH3) - 、SO3(OC2H5) - 、SO3[OCH(CH3)] - 、SO3(OC4H9) - wait.
[0127] The anion components exemplified above can be used alone or in combination of two or more.
[0128] In addition, when the ionomer is an ionic liquid, the electrode catalyst layer 12 may contain a fixing agent. By containing the fixing agent, the ionic liquid is fixed in the electrode catalyst layer 12, thereby maintaining its shape and position. As a result, it is possible to suppress the ionic liquid from clogging the gaps, and the fluid can flow well in the electrode catalyst layer 12. As a result, a three-phase interface can be formed well in the electrode catalyst layer 12.
[0129] The thickness of the electrode catalyst layer 12 is not particularly limited, and is generally 0.1 to 100 μm, preferably 1 to 50 μm. By making the thickness of the electrode catalyst layer 12 0.1 μm or more, the power generation required by the fuel cell can be obtained. On the other hand, by making the thickness of the electrode catalyst layer 12 100 μm or less, the resistance of the gas diffusion of hydrogen or oxygen in the electrode catalyst layer 12 can be suppressed, and the by-product water can also be discharged well. As a result, the power generation performance of the fuel cell can be further improved.
[0130] The method for preparing the electrode catalyst layer 12 is not particularly limited, and a known method can be used. For example, the following method can be cited: the fuel cell catalyst and ionomer (electrolyte with proton conductivity) of the present embodiment are dissolved in water or an organic solvent to obtain a catalyst ink, which is directly applied to the solid polymer electrolyte membrane 11 and dried to form the electrode catalyst layer 12. Alternatively, the following method can also be cited: the catalyst ink is applied to a sheet made of polytetrafluoroethylene (PTFE), the catalyst ink is dried, and then transferred to the solid polymer electrolyte membrane 11 by hot pressing to form the electrode catalyst layer 12.
[0131] The organic solvent for dispersing the fuel cell catalyst and the ionomer of the present embodiment is not particularly limited, and examples thereof include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, tert-butanol, pentanol, acetone, methyl ethyl ketone, pentanone, methyl isobutyl ketone, heptanone, cyclohexanone, methyl cyclohexanone, acetonylacetone, diisobutyl ketone, tetrahydrofuran, dioxane, diethylene glycol dimethyl ether, anisole, methoxytoluene, dibutyl ether, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, diethylene glycol, diacetone alcohol, 1-methoxy-2-propanol, and the like.
[0132] The mixing ratio of the fuel cell catalyst and the ionomer in the catalyst ink is not particularly limited. Usually, the mass ratio of the ionomer to the carrier of the fuel cell catalyst (containing fluorine atoms when the carrier is fluorinated) is 30 to 200 weight%, preferably 40 to 150 weight%, and more preferably 50 to 120 weight%. By making the mass ratio of the ionomer to the carrier of the fuel cell catalyst 30% or more, the structure of the anode side electrode catalyst layer 12a and the cathode side electrode catalyst layer 12b formed is stable, and the ion conductivity in the electrode catalyst layer 12 can be good. In addition, by making the mass ratio of the ionomer to the carrier of the fuel cell catalyst 200% or less, it is possible to suppress the surface of the catalytically active substance from being excessively covered by the ionomer. As a result, a good three-phase interface can be formed.
[0133] In addition, there is no particular limitation on the method of dispersing the fuel cell catalyst and the electrolyte into the solvent, and for example, they can be dispersed using a known dispersing device such as a ball mill, a dissolver, an ultrasonic homogenizer, a high-pressure homogenizer, etc. In addition, there is no particular limitation on the method of drying the catalyst ink, and the catalyst ink can be dried by natural drying, hot air drying, ultraviolet drying, etc. Moreover, there is no particular limitation on the drying conditions such as the drying time and the drying temperature, and they can be appropriately set according to the concentration of the catalyst ink, the coating amount, etc.
[0134] <Gas Diffusion Layer>
[0135] The gas diffusion layer 13 is composed of a porous body having electronic conductivity. By having electronic conductivity, electrons from the reaction of the fuel cell can be moved. In addition, by being composed of a porous body, hydrogen contained in the fuel gas can be well diffused in the anode side gas diffusion layer 13a, and air contained in the oxidant gas can be well diffused in the cathode side gas diffusion layer 13b. Moreover, in the cathode side electrode catalyst layer 12b, it also functions as a discharge channel for discharging by-product water.
[0136] The material of the gas diffusion layer 13 is not particularly limited, but is preferably a material that is inert to the hydrogen contained in the fuel gas and the air contained in the oxidant gas, has high fluid diffusivity, has corrosion resistance, and has high electronic conductivity. Examples of such materials include carbon paper such as Torayca (registered trademark, Toray Industries, Inc.) or Pyrofil (registered trademark, Mitsubishi Rayon Co., Ltd.), carbon cloth, and porous substrates.
[0137] The thickness of the gas diffusion layer 13 in the present invention is not particularly limited, and is generally 50 to 500 μm, preferably 100 to 300 μm. By making the thickness of the gas diffusion layer 13 50 μm or more, it is possible to maintain the mechanical strength of the gas diffusion layer 13. In addition, by making the gas diffusion layer 13 500 μm or less, it is possible to suppress the resistance of gas diffusion in the gas diffusion layer 13, and it is possible to discharge the by-product water well. As a result, it is possible to improve the power generation performance of the fuel cell.
[0138] <Diaphragm>
[0139] The material of the diaphragm 14 is not particularly limited, and is preferably a material that is inert to the hydrogen contained in the fuel gas and the air contained in the oxidant gas, has high gas sealing properties, and is corrosion-resistant. In addition, a material with high electronic conductivity and excellent mechanical strength is preferred. As such a material, for example, a carbon diaphragm composed of isotropic carbon, carbon plates, etc. can be cited. In addition, a diaphragm made of metal such as stainless steel can be cited. Moreover, a diaphragm formed by coating a carbon material on the surface of a part made of metal such as stainless steel, titanium or aluminum can also be used. It should be noted that as the diaphragm 14, it is preferred to have a diaphragm that has the function of separating hydrogen as a fuel from air, thereby forming a gas flow channel on the surface. In addition, the thickness of the diaphragm 14 is not particularly limited and can be appropriately set as needed.
[0140] <Spacer>
[0141] The gasket 15 is located between the solid polymer electrolyte membrane 11 and the diaphragm 14 at a position adjacent to the ends of the electrode catalyst layer 12 and the gas diffusion layer 13. By providing the fuel cell 1 with the gasket 15, the ends of the electrode catalyst layer 12 and the gas diffusion layer 13 are sealed, and the supplied gas can be prevented from leaking from the ends of the electrode catalyst layer 12 and the gas diffusion layer 13.
[0142] When manufacturing the fuel cell 1, pressure is generated from the diaphragms 14 on both sides toward the center (toward the solid polymer electrolyte membrane 11), but by providing the gasket 15, the gaps in the electrode catalyst layer 12 and the gas diffusion layer 13 can be prevented from being crushed by the pressure.
[0143] As the gasket 15, a known material that is inert to hydrogen contained in the fuel gas and air contained in the oxidant gas, has high gas sealing properties, has little expansion and contraction displacement relative to the pressure when assembling the single cell, and has good dimensional stability can be used. For example, rubber materials such as fluororubber, silicone rubber, ethylene propylene rubber (EPDM), and polyisobutylene rubber, fluorine-based polymer materials such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyhexafluoropropylene, and tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and thermoplastic resins such as polyolefins or polyesters can be cited.
[0144] The thickness of the spacer 15 is not particularly limited, and can be appropriately set according to the thickness of the electrode catalyst layer 12 and the thickness of the gas diffusion layer 13 .
[0145] Example
[0146] Hereinafter, preferred embodiments of the present invention will be described in detail by way of example. However, the materials, blending amounts, etc. described in the embodiments are not intended to limit the scope of the present invention to these unless otherwise specified.
[0147] (Example 1)
[0148] <Fluorination treatment of carrier>
[0149] A PTFE (polytetrafluoroethylene) container (capacity 5 mL) was added with a specific surface area of 800 m 2 / g of carbon black (trade name; Ketjen Black EC300J, LION SPECIALTY CHEMICALS Co., Ltd.) 0.300g, and the container is set in a chamber (capacity 30mL) made of SUS316L after electrolytic polishing. Then, after the chamber is evacuated, nitrogen gas is introduced (vacuum replacement). Under nitrogen flow (20mL / min), the temperature in the chamber is raised to 250°C at a heating rate of 4°C / min, and the temperature is kept constant for 1 hour. Then, the temperature in the chamber is cooled to 50°C and the temperature is kept constant for 1 hour.
[0150] Next, the temperature in the chamber is maintained at 50°C, and the nitrogen is removed by vacuuming. Then, a mixed gas (processing gas) in which fluorine (F2) gas is diluted by nitrogen to a concentration of 10 vol% is introduced into the chamber (vacuum replacement). Thus, the carbon black is fluorinated. The treatment conditions for the fluorination treatment are a treatment time of 4 hours, a treatment temperature of 50°C, and a treatment pressure of normal pressure. Then, the chamber is made into a vacuum (10Pa) to remove the mixed gas, and then nitrogen is introduced (vacuum replacement). Then, it is cooled to room temperature under a nitrogen flow (20mL / min). Thus, fluorinated carbon black (i.e., carbon black into which fluorine atoms have been introduced) is produced.
[0151] <Production of fuel cell catalyst>
[0152] 0.300 g of fluorinated carbon black was added to 100 mL of an aqueous solution containing 0.797 g of chloroplatinic acid hexahydrate (H2PtCl6·6H2O), and the carrier was dispersed in the aqueous solution using an ultrasonic homogenizer. 1 mol / L of sodium hydroxide aqueous solution was added to the dispersion to adjust the pH to a range of 11 to 12.
[0153] Next, the dispersion was heated to 90°C under N2 atmosphere, and NaBH4 solution was added to reduce platinum. The reduced dispersion was subjected to solid-liquid separation, the obtained crystals were washed, and then vacuum dried at 90°C to prepare a fuel cell catalyst loaded with platinum.
[0154] (Example 2)
[0155] In this example, the fuel cell catalyst of this example was prepared in the same manner as in Example 1 except that the concentration of fluorine gas in the treatment gas during the fluorination treatment was changed to 5 vol%.
[0156] (Example 3)
[0157] In this example, the fuel cell catalyst of this example was prepared in the same manner as in Example 1 except that the concentration of fluorine gas in the treatment gas during the fluorination treatment was changed to 20 vol%.
[0158] (Comparative Example 1)
[0159] In this comparative example, a platinum-supported catalyst (product number: TEC10E50E, manufactured by Tanaka Kikinzoku Co., Ltd.) in which platinum is supported on Ketjen black (support) which has not been subjected to a fluorination treatment was used as a fuel cell catalyst.
[0160] (Example 4)
[0161] In this example, the concentration of fluorine gas in the treatment gas during the fluorination treatment was changed to 80 vol%, and the treatment temperature was changed to 80° C. Except for this, the same operation as in Example 1 was carried out to prepare a fuel cell catalyst in this example.
[0162] (Example 5)
[0163] In this example, a platinum-supported catalyst (product number: TEC10E50E, manufactured by Tanaka Precious Metals Co., Ltd.) in which platinum is supported on the Ketjen black (carrier) that has not been subjected to fluorination treatment is subjected to fluorination treatment. In addition, the concentration of fluorine gas in the treatment gas during the fluorination treatment is changed to 10 vol%. Other than this, the fuel cell catalyst in this example is prepared in the same manner as in Example 1.
[0164] (Example 6)
[0165] In this example, the fuel cell catalyst obtained in Example 2 was subjected to fluorination treatment again. The conditions for the re-fluorination treatment were the same as those in Example 1, and the fuel cell catalyst in this example was produced.
[0166] (Platinum content in fuel cell catalyst)
[0167] In the fuel cell catalysts obtained in Examples 1 to 6 and Comparative Example 1, the platinum content relative to the total mass of each fuel cell catalyst was determined. That is, each fuel cell catalyst was burned in an oxygen atmosphere at 800° C. using an electric furnace. The remaining amount after combustion was taken as the amount of platinum, and the platinum content was calculated from the weight before combustion. The results are shown in Table 1.
[0168] (Elemental analysis of fuel cell catalyst surface)
[0169] For the fuel cell catalysts obtained in Examples 1 to 6, a quantitative analysis of the fluorine atoms and carbon atoms on their surfaces was performed. A multifunctional scanning X-ray photoelectron spectrometer (VersaProbeIII manufactured by ULVAC-PHI Co., Ltd.) was used to perform quantitative analysis by X-ray photoelectron spectroscopy. The measurement conditions were as follows: X-ray source: AlKα ray, pass energy: 112 eV, step energy: 0.05 eV, detection angle: 45°. The ratio of the number of fluorine atoms to carbon atoms on the surface of each fuel cell catalyst (F / C) was then calculated from the peak intensity of the photoelectron spectra of C1s and F1s. S The results are shown in Table 1.
[0170] (Elemental analysis of the entire fuel cell catalyst)
[0171] The fuel cell catalysts obtained in Examples 1 to 6 were subjected to quantitative analysis of fluorine atoms and carbon atoms in the entire fuel cell catalyst. The quantitative analysis was performed by a combustion flask method.
[0172] That is, each fuel cell catalyst was burned in a sealed flask container with a volume of 500 mL filled with oxygen. Next, the gas generated by the combustion was absorbed by a sample solution (a mixed aqueous solution of 1.7 mmol / L sodium bicarbonate and 1.8 mmol / L sodium carbonate) in the flask, and the content of fluoride ions contained in the test solution was quantified using an ion chromatograph (ICS-1000, Dionex, chromatographic column AS-23).
[0173] Next, the content of fluorine atoms in the entire fuel cell catalyst is calculated from the quantitative fluorine ion content. Furthermore, the amount after deducting the platinum content converted based on the above-mentioned platinum content and the content of fluorine atoms in the entire fuel cell catalyst from the mass of the fuel cell catalyst is calculated and used as the content of carbon atoms in the entire fuel cell catalyst. Thus, the ratio of the number of fluorine atoms in the entire fuel cell catalyst to the number of carbon atoms (F / C) is calculated. W , and then calculate (F / C) S / (F / C) W The results are shown in Table 1.
[0174] (Work function of fuel cell catalyst)
[0175] For the fuel cell catalysts of Examples 1 to 6 and Comparative Example 1, the work functions of each were obtained. The work function was obtained by ultraviolet photoelectron spectroscopy using a multifunctional scanning X-ray photoelectron spectrometer (Versa Probe III, manufactured by ULVAC-PHI Co., Ltd.). In addition, the measurement conditions were ultraviolet source: HeI rays, pass energy: 1.3 eV, step energy: 0.005 eV, and detection angle: 90°. Then, the energy difference between the binding energy and the vacuum energy level was obtained, and the work function of each fuel cell catalyst was calculated. The results are shown in Table 1.
[0176] [Table 1]
[0177]
[0178] (Manufacturing of fuel cells)
[0179] <Production of cathode electrode catalyst layer>
[0180] Based on the platinum content in the fuel cell catalyst of Examples 1 to 6 or Comparative Example 1, the fuel cell catalyst was weighed so that the platinum content was 16 mg. Next, a Nafion (registered trademark) solution (manufactured by DuPont, DE520CS Type) was added as an ionomer. The addition of the ionomer was 70% by mass relative to the mass of the carrier excluding platinum and fluorine atoms in the fuel cell catalyst.
[0181] Next, a mixed solvent of ultrapure water and 2-propanol at a volume ratio of 1:1 was added to the mixture of the fuel cell catalyst and the ionomer. At this time, the mixed solvent was added so that the solid content of the fuel cell catalyst and the ionomer was 5% by mass. Then, the fuel cell catalyst and the ionomer were dispersed for 30 minutes by an ultrasonic homogenizer to prepare the catalyst ink in each of Examples 1 to 6 and Comparative Example 1.
[0182] Next, the prepared catalyst ink was applied to a PTFE (polytetrafluoroethylene) sheet and dried. Thus, the cathode side electrode catalyst layer in each of Examples 1 to 6 and Comparative Example 1 was formed on the PTFE sheet. It should be noted that the unit mass of platinum in the formed electrode catalyst layer was 0.25 mg / cm 2 The coating amount of the catalyst ink is set in this way.
[0183] <Production of Anode-Side Electrode Catalyst Layer>
[0184] A commercially available platinum-supported catalyst (product number: TEC10E50E, Tanaka Kikinzoku Co., Ltd.) was weighed so that the platinum content was 16 mg. Next, a Nafion (registered trademark) solution (manufactured by DuPont, DE520CS Type) was added as an ionomer. The ionomer was added so that the mass of the carrier other than platinum in the fuel cell catalyst was 100 mass %.
[0185] Next, a mixed solvent of ultrapure water and 2-propanol in a volume ratio of 1:1 was added to the mixture of the fuel cell catalyst and the ionomer. At this time, the mixed solvent was added so that the solid content of the platinum-supported catalyst and the ionomer was 5% by mass. Then, the platinum-supported catalyst and the ionomer were dispersed for 30 minutes using an ultrasonic homogenizer to prepare a catalyst ink.
[0186] Next, the prepared catalyst ink was applied to a PTFE sheet and dried. Thus, an anode-side electrode catalyst layer was formed on the PTFE sheet. It should be noted that the unit mass of platinum in the formed electrode catalyst layer was 0.25 mg / cm 2 The coating amount of the catalyst ink is set in this way.
[0187] <Assembly of fuel cell>
[0188] The anode electrode catalyst layer formed on the PTFE sheet and the cathode electrode catalyst layer formed on the PTFE sheet were cut into 1 cm squares and laminated on both surfaces of a solid polymer electrolyte membrane (NR-211, DuPont) to prepare a laminate.
[0189] Next, the laminate was pressed at 150°C and 1.2 MPa for 3 minutes, and the anode side electrode catalyst layer and the cathode side electrode catalyst layer formed on the PTFE sheet were transferred to the solid polymer electrolyte membrane. Then, the PTFE sheet was peeled off. By this method, membrane electrode assemblies using the fuel cell catalysts in Examples 1 to 6 and Comparative Example 1 were prepared respectively. At this time, the thickness of the anode side electrode catalyst layer and the cathode side electrode catalyst layer were 7 μm, respectively, and the thickness of the solid polymer electrolyte membrane was 25 μm.
[0190] Furthermore, a pair of gas diffusion layers (TGP-H-060, manufactured by Toray Industries, Inc.) were arranged so as to sandwich each membrane electrode assembly, and the gas diffusion layers (thickness 190 μm) were stacked.
[0191] Next, a sandwiching separator having grooves formed therein as gas flow paths was arranged on both surfaces of a pair of gas diffusion layers, thereby producing fuel cell units in Examples 1 to 6 and Comparative Example 1.
[0192] (Output voltage evaluation)
[0193] For the fuel cell units in Examples 1 to 6 and Comparative Example 1, the initial output voltage was evaluated.
[0194] That is, in the obtained fuel cell, hydrogen was supplied to the anode side at normal pressure (utilization rate 5%), and oxygen was supplied to the cathode side by supplying air (utilization rate 5%). The relative humidity in the cell was 60% RH. The current density during operation was measured at a cell temperature of 80°C and was 1.0 A / cm -2 The results are shown in Table 2.
[0195] (Start and stop of fuel cell)
[0196] The temperature of the fuel cell was set to 80°C, humidification control was performed so that the relative humidity in the cell was 100% RH, and nitrogen gas was supplied to each of the anode side and the cathode side.
[0197] Next, the potential scan was repeated in the potential range of 1.0 to 1.5 V at a potential scan rate of 0.5 V / s, and this was used as a potential scan cycle to simulate the start and stop of each fuel cell. After 1500 cycles, the output voltage of each fuel cell was measured. The measurement method was the same as in the above case. The results are shown in Table 2.
[0198] [Table 2]
[0199]
[0200] Explanation of symbols
[0201] 1 Fuel Cell
[0202] 10 Membrane Electrode Assembly
[0203] 11 Solid polymer electrolyte membrane
[0204] 12 Electrode catalyst layer
[0205] 12a Anode side electrode catalyst layer
[0206] 12b Cathode side electrode catalyst layer
[0207] 13 Gas Diffusion Layer
[0208] 13a Anode side gas diffusion layer
[0209] 13b Cathode side gas diffusion layer
[0210] 14 Diaphragm
[0211] 15 Gasket.
Claims
1. A catalyst for a fuel cell, characterized in that: At least having a catalytically active substance and a carrier for supporting the catalytically active substance, The catalytically active material is at least one selected from platinum, a platinum alloy, and a core-shell catalyst in which a core of a metal different from platinum is covered with a shell containing platinum, The carrier is a carbon material, At least one of the catalytically active material and the carrier contains fluorine atoms, The fluorine atoms contained in the catalytically active substance are adsorbed on the surface of the catalytically active substance. The fluorine atoms contained in the carrier are adsorbed on the outer surface of the carbon material as the carrier and the inner surface of the pores. The content of the fluorine atoms is 0.1 to 30% by mass relative to the total mass of the fuel cell catalyst. The ratio of the number of fluorine atoms contained in at least one of the catalytically active material and the carrier to the number of carbon atoms contained in the carrier satisfies the relationship represented by the following formula (1): (F / C) S / (F / C) W <0.8···(1) Among them, (F / C) S The ratio of the number of fluorine atoms on the surface of the fuel cell catalyst to the number of carbon atoms (F / C) W It indicates the ratio of the number of fluorine atoms to the number of carbon atoms in the entire fuel cell catalyst.
2. The fuel cell catalyst according to claim 1, wherein Said (F / C) S Less than 0.
4.
3. The fuel cell catalyst according to claim 1, wherein The carbon material is at least one selected from graphite, graphite oxide, carbon black, graphitized carbon black, diamond-like carbon, fullerene, single-walled carbon nanotube, multi-walled carbon nanotube, carbon nanohorn, carbon nanowall, carbon nanofiber, carbon nanobrush, single-layer graphene, multi-layer graphene, and graphene oxide.
4. The fuel cell catalyst according to claim 1, wherein The work function is in the range of 4 to 7.5 eV.
5. A membrane electrode assembly for a fuel cell, characterized in that: The fuel cell membrane electrode assembly comprises at least a solid polymer electrolyte membrane and electrode catalyst layers disposed on both surfaces of the solid polymer electrolyte membrane. The electrode catalyst layer at least comprises a fuel cell catalyst and an ionomer covering the fuel cell catalyst. The fuel cell catalyst comprises at least a catalytically active substance and a carrier that supports the catalytically active substance. The catalytically active material is at least one selected from platinum, a platinum alloy, and a core-shell catalyst in which a core of a metal different from platinum is covered with a shell containing platinum, The carrier is a carbon material, At least one of the catalytically active material and the carrier contains fluorine atoms, The fluorine atoms contained in the catalytically active substance are adsorbed on the surface of the catalytically active substance. The fluorine atoms contained in the carrier are adsorbed on the outer surface of the carbon material as the carrier and the inner surface of the pores. The content of the fluorine atoms is 0.1 to 30% by mass relative to the total mass of the fuel cell catalyst. The ratio of the number of fluorine atoms contained in at least one of the catalytically active material and the carrier to the number of carbon atoms contained in the carrier satisfies the relationship represented by the following formula (1): (F / C) S / (F / C) W <0.8···(1) Among them, (F / C) S The ratio of the number of fluorine atoms on the surface of the fuel cell catalyst to the number of carbon atoms (F / C) W It indicates the ratio of the number of fluorine atoms to the number of carbon atoms in the entire fuel cell catalyst.
6. The membrane electrode assembly for fuel cell according to claim 5, wherein: Said (F / C) S Less than 0.
4.
7. The membrane electrode assembly for a fuel cell according to claim 5, wherein: The carbon material is at least one selected from graphite, graphite oxide, carbon black, graphitized carbon black, diamond-like carbon, fullerene, single-walled carbon nanotube, multi-walled carbon nanotube, carbon nanohorn, carbon nanowall, carbon nanofiber, carbon nanobrush, single-layer graphene, multi-layer graphene, and graphene oxide.
8. The membrane electrode assembly for a fuel cell according to claim 5, wherein: The work function is in the range of 4 to 7.5 eV.
9. The membrane electrode assembly for a fuel cell according to claim 5, wherein: The ionomer is a fluorine-based resin.
10. The fuel cell membrane electrode assembly according to claim 5, wherein: The ionomer is an aromatic hydrocarbon resin.
11. The fuel cell membrane electrode assembly according to claim 5, wherein: The ionomer is an ionic liquid.
12. A fuel cell, characterized in that: A fuel cell membrane electrode assembly according to claim 5 is provided.
Citation Information
Patent Citations
Solid polymer fuel cell catalyst, and electrode and battery using the same
JP2012079489A
Fluorine-containing carbon particles, method for producing same, and use thereof
WO2016190248A1
Electrode catalyst layer for fuel cells, electrode for fuel cells, membrane electrode assembly for fuel cells, and fuel cell
CN103765643A
Fuel cell
JP2005243583A
Carbon material and method for manufacturing same
WO2017217331A1